Dynamics of directional soluble wicking. (16th March 2021) - Jung, Sohyun; Kim, Wonjung; Kim, Ho-Young
Abstract: Abstract : Liquids can invade fibrous porous media when the fibres are either wettable or soluble, and the infiltration rate can differ depending on spatial distribution of fibres as well as liquid properties. With continuing developments in dissolution-driven release mechanisms of porous drugs and chemical pattern formations, the understanding of how liquids spontaneously infiltrate into soluble fibrous media is strongly called for. Here we show that unlike capillarity-driven insoluble wicking (exhibiting diffusive growth of wetting distance with time), the wicking distance in soluble porous media grows linearly with time as dominated by liquid viscosity rather than surface tension. Such soluble wicking is highly sensitive to flow orientation relative to fibre alignment, so that it arises only in the crosswise direction while being strongly inhibited in the lengthwise direction. We present a theoretical model to explain the experimentally measured wicking rates in soluble porous media.